PENINGKATAN LITERASI DIGITAL MELALUI PKM DI SMP NEGERI 19 DEPOK : MENGINSPIRASI GENERASI MUDA - Regina Maurita Rianto Putri; Ahmad Fa’idh Rifa’i; Almira Safana; Devina Azzahra Putri; Dini Juniarti; Marcelino; Nazua Ditania; Rafli Arabiansyah; Raya Adinda Jayadi Ahmad; Rohimat; Santi Rahayu (Abdi Jurnal Publikasi, 2024)
The advancement of technology has transformed human activities, especially in the fields of technology and communication. However, this convenience has been misused by some individuals to commit crimes, such as cyberbullying. Cyberbullying is a new form of bullying that involves the use of electronic media. It is defined as negative activities intentionally and repeatedly carried out to harm others through various electronic platforms, such as social networks, chat rooms, emails, and mobile phones, often involving threatening or offensive messages. This issue is frequently experienced by teenagers who are active internet users, including those in junior high school. Based on this problem, this PKM program aims to educate students of SMP Negeri 19 Depok on preventing cyberbullying behavior and the importance of maintaining a positive digital footprint. This program is designed to raise students' awareness of the impacts of cyberbullying, both on victims and perpetrators, and to provide effective strategies to avoid involvement in such activities. Furthermore, the program focuses on managing digital footprints to help students understand the long-term consequences of their online actions. Through interactive approaches such as seminars, group discussions, and case simulations, students are expected to become more responsible in using technology and communicating online. Thus, this program not only helps prevent cyberbullying but also fosters a healthier digital culture within the school environment.